2017
DOI: 10.3390/en10070910
|View full text |Cite
|
Sign up to set email alerts
|

Production of Torrefied Solid Bio-Fuel from Pulp Industry Waste

Abstract: The pulp industry in Taiwan discharges tons of wood waste and pulp sludge (i.e., wastewater-derived secondary sludge) per year. The mixture of these two bio-wastes, denoted as wood waste with pulp sludge (WPS), has been commonly converted to organic fertilizers for agriculture application or to soil conditioners. However, due to energy demand, the WPS can be utilized in a beneficial way to mitigate an energy shortage. This study elucidated the performance of applying torrefaction, a bio-waste to energy method,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Huang et al used a laboratory scale batch reactor to perform the torrefaction of waste from pulp industries [26]. The obtained energy densification ratios varied between 1.26 and 1.5, depending on the process parameters [26].…”
Section: Torrefaction Of Sewage Sludgementioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al used a laboratory scale batch reactor to perform the torrefaction of waste from pulp industries [26]. The obtained energy densification ratios varied between 1.26 and 1.5, depending on the process parameters [26].…”
Section: Torrefaction Of Sewage Sludgementioning
confidence: 99%
“…Huang et al used a laboratory scale batch reactor to perform the torrefaction of waste from pulp industries [26]. The obtained energy densification ratios varied between 1.26 and 1.5, depending on the process parameters [26]. Huang et al investigated the microwave co-torrefaction of sewage sludge with Leucaena and noticed a synergetic effect of the use of combined feedstocks for torrefaction [27,28].…”
Section: Torrefaction Of Sewage Sludgementioning
confidence: 99%
“…Some amount of work on thermal treatment for utilization of the sewage sludge has been performed, including some fundamental work, using thermogravimetric analysis [20,21]. Huang et al torrefied waste from pulp industries in a laboratory scale, batch reactor and determined energy densification ratios varying from 1.26 up to 1.5 depending on the process conditions [22]. Studies performed by Huang et al on microwave co-torrefaction of sewage sludge with leucaena reported synergistic effect between the two feedstocks, during torrefaction [23,24].…”
Section: Dry and Wet Torrefaction And Pyrolysis Of Sewage Sludgementioning
confidence: 99%
“…Heat obtained this way was recovered in HRSG to generate steam for a steam turbine. Some operational problems have been reported [22,24]: cold spots in the coke bed, due to inadequate penetration by plasma torches [49]; too short life span of the refractory of the reactor-caused by adding additional refractory to remediate the problem of the cold spots [49]; erosion of the refractory of the after-burner (which caused the operator to lower the exit temperature of syngas from 1200 • C to 750 • C) [49]. Reactor requires auxiliary substances to operate.…”
Section: Slagging Gasifier As a Feasible Tool For Gasification And Inmentioning
confidence: 99%
“…Globally, biomass fuel is becoming more and more attractive as a suitable substitute for fossil fuels due to the increasing demand for clean energy [2][3][4]. Furthermore, biomass is a renewable energy source, and its importance will increase as national energy policies and strategies focus more heavily on renewable sources and conservation [5].…”
Section: Introductionmentioning
confidence: 99%